THE INFLUENCE OF INTERNSHIP EXPERIENCE, SOCIAL SUPPORT, AND WORK MOTIVATION ON WORK READINESS OF FEB STUDENTS OF UNIVERSITAS TARUMANAGARA - Vilysia Vilysia; Joyce A. Turangan (International Journal of Application on Economics and Business, 2024)
This study was conducted with the aim of knowing the effect of internship experience, social support and work motivation on the work readiness of FEB Tarumanagara University students. This study is a quantitative descriptive study with a cross-sectional method. The population in this study were all students of the Faculty of Economics and Business, Tarumanagara University. Sample selection was carried out using non-probability sampling method with purposive sampling sample selection technique. In this study, there are criteria for selecting samples such as having done an internship and being an active student at Tarumanagara University. The total sample in this study was 81 samples. From the data obtained, data processing will be carried out through SmartPLS software with the structural equation modeling (SEM) method of it. The result of the study shows through hypothesis testing that all the independent variable have a positive effect on Tarumanagara University students.